Interdisciplinary discourse on transformations of musical culture in a global context - Dmytro Terentiev; Olga Zaiats; Dennis Adu; Pavlo Halytskyi; Borys Mohylevskyi (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
The article examines the impact of globalization and digitalization on the development of contemporary musical art. Rapid advances in information technologies have transformed music into a key element of the global cultural space, facilitating interaction among diverse cultures, traditions, and creative practices. The study analyzes how the Internet, streaming services, social media, and artificial intelligence have reshaped the creation, distribution, and consumption of music. Particular attention is paid to the role of digital platforms in promoting musical works, supporting artists, and influencing audience preferences through recommendation algorithms. The paper highlights the growing integration of musical styles and traditions across countries, fostering intercultural dialogue and the emergence of new artistic forms. At the same time, local cultural characteristics remain essential for preserving national identity within a globalized environment. The research also explores innovative trends, including AI-generated music, virtual concerts, and the use of music in education and therapy. While digital technologies expand creative opportunities and public access to cultural content, challenges such as copyright infringement, unequal revenue distribution, and cultural homogenization persist. The article concludes that musical art is a dynamic system shaped by technological, social, and cultural changes, requiring a balance between innovation, economic sustainability, and cultural diversity.